Ancient and modern mitogenomes from Central Argentina: new insights into population continuity, temporal depth and migration in South America. Issue 13 (15th April 2021) - García, Angelina; Nores, Rodrigo; Motti, Josefina M B; Pauro, Maia; Luisi, Pierre; Bravi, Claudio M; Fabra, Mariana; Gosling, Anna L; Kardailsky, Olga; Boocock, James; Solé-Morata, Neus; Matisoo-Smith, Elizabeth A; et al.
Abstract: The inverted triangle shape of South America places Argentina territory as a geographical crossroads between the two principal peopling streams that followed either the Pacific or the Atlantic coasts, which could have then merged in Central Argentina (CA). Although the genetic diversity from this region is therefore crucial to decipher past population movements in South America, its characterization has been overlooked so far. We report 92 modern and 22 ancient mitogenomes spanning a temporal range of 5000 years, which were compared with a large set of previously reported data. Leveraging this dataset representative of the mitochondrial diversity of the subcontinent, we investigate the maternal history of CA populations within a wider geographical context. We describe a large number of novel clades within the mitochondrial DNA tree, thus providing new phylogenetic interpretations for South America. We also identify several local clades of great temporal depth with continuity until the present time, which stem directly from the founder haplotypes, suggesting that they originated in the region and expanded from there. Moreover, the presence of lineages characteristic of other South American regions reveals the existence of gene flow to CA. Finally, we report some lineages with discontinuous distribution across the Americas, which suggest the persistence of relic lineages likely linked to the first population arrivals. The present study represents to date the most exhaustive attempt to elaborate a Native American genetic map from modern and ancient complete mitochondrial genomes in Argentina and provides relevant information about the general process of settlement in South America.